Optimalisasi Perawatan Sekoci Penolong Sebagai Penunjang Keselamatan Awak Kapal - Kevin Pratama; Arleiny Arleiny; Eko Nugroho Widjatmoko (Politeknik Ilmu Pelayaran Semarang, 2022)
Safety equipment is an important aspect in supporting the security of a voyage. The importance of having safety equipment, especially Lifeboats on board, is a serious matter that cannot be underestimated. Carrying out regular maintenance of safety equipment is an effort to prevent and overcome marine transportation accidents. The maintenance and operation of lifeboats is not just a routine, but is a series of activities for the crew that requires a lot of attention and is supported by good manpower management. The purpose of this study was to describe the level of knowledge of the crew regarding the maintenance of lifeboats and their impact on the safety of the crew. This study uses qualitative methods, data collection is carried out by interviewing the crew, documentation, and conducting observations to obtain primary data and will then be used as guidelines for drawing conclusions. The results showed that the maintenance of lifeboat safety equipment according to procedures had an important influence in reducing the risk of accidents and fatalities.